Photoluminescence temperature dependence of doped parabolic quantum wells - Tabata, Américo Sheitiro [UNESP]; Martins, M. R.; Oliveira, José Brás Barreto de [UNESP]; Lamas, T. E.; Duarte, C. A.; Quivy, A. A.; Gusev, G. M. (Wiley-Blackwell, 2007)
Parabolic quantum wells (PQWs) have been studied by temperature dependent photoluminescence (PL). Two kind of samples have been studied. Concerning the undoped sample, the dominant luminescences were the bulk GaAs and the fundamental transition of the PQW. The evolution on temperature of the energy position of both PL emissions follows the well known Varshing formula. For the doped samples strong radiative recombination of the electron gas with photogenerated holes was observed. At low temperature strong Fermi level enhancement occurs in the luminescence as a result of the multi-electron-hole scattering, which is smear out increasing the temperature.